FEKUNDITAS DAN POLA PERKEMBANGAN GONAD IKAN TAJUK EMAS, Pristipomoides multidens, Day 1871DIPERAIRAN PALABUHANRATU, JAWA BARAT [Fecundity and Gonad Maturity of Pristipomoides multidens, Day 1871 in Palabuhan Ratu Waters, West Java] - F. Damianus Hukom; Ridwan Affandi; Saddon Silalahi; Iska Angelika (Jurnal Iktiologi Indonesia, 2006)
The observation was done in Palabuhanratu bay from June 2005 until February 2006, The observation aimed to describe fecundity and development of the gonad. Samples were caught using hand lines with 6-9 mesh size and “kincang” boat. Total sample were 108 with range of length are 210 - 812 mm and total weight between 62 - 6434 gram. Fecundity was between 205.547 - 3.028.159 and shown that P. multidens had a large reproductive potency. The development of gonad (testes and ovary) in morphology and histology could explained the first size sexual maturity, spawning season and spawning type.